Optimization parameters to prepare chitosan nanoparticles containing sulfacetamide sodium - Zahra Sobhani; Soliman Mohammadi-Samani; Mohammad Reza Arazi (Shiraz University of Medical Sciences, 2020)
Management of ocular disease can be improved by prolonging the contact time of ophthalmic antibiotics with the ocular surface using bioadhesive polymers such as chitosan. Additionally, this polymer with antifungal and antibacterial activities could increase the antimicrobial effects of the antibiotics. In the present study, chitosan (CS) nanoparticles were investigated as a vehicle for ophthalmic delivery of sulfacetamide sodium. The ionotropic gelation method was used to fabricate chitosan -sulfacetamide sodium nanoparticles.  The effects of various factors including the concentration of CS, concentration of tripolyphosphate (TPP), and stirrer rate on the size of nanoparticles were studied. Different weight ratio of CS to sulfacetamide sodium on the encapsulation efficiencies of nanoparticles was assessed. The particles were prepared under the optimal condition of 0.45% CS concentration, 0.45% TPP concentration, stirrer rate at 6000 rpm. Their particle size was 72nm. In these particles with a 1:2 weight ratio of CS to sulfacetamide sodium, the encapsulation efficiency was 42%. In vitro release profile showed that sulfacetamide sodium could not be released sufficiently for 24 h. Future studies should focus on in vitro and in vivo antibacterial properties to evaluate their potential as an ocular delivery system.